Pengaruh Sarana dan Prasarana Terhadap Kepuasan Wisatawan di Taman Hutan Raya Ir. H. Djuanda - Rieke Sri Rizki Asti Karini; Rivaldo Rahman Nugraha (Manajemen dan Pariwisata, 2026)
Ir. H. Djuanda Dago Grand Forest Park is one of the tourist destinations in Bandung. This research is motivated by the importance of the quality of facilities and infrastructure in supporting the comfort and satisfaction of tourists at natural tourism destinations. This area is one of the favorite tourist attractions in Bandung City with great natural potential, yet it still faces challenges related to maintenance and facility development. The purpose of this study is to determine the extent of the influence of facilities and infrastructure on tourist satisfaction. The method used is quantitative, with data collected through questionnaires distributed to 100 respondents. The variables studied include facilities, infrastructure, and tourist satisfaction, measured using a 1–5 Likert scale. The data obtained from the questionnaires were processed using SPSS Statistics 30 software. The results show that both partially and simultaneously, facilities and infrastructure have a positive and significant influence on tourist satisfaction. The conclusion of this study is that improving the quality and availability of facilities and infrastructure can significantly enhance tourist satisfaction. These findings provide useful recommendations for management to improve the quality of nature-based tourism services at Tahura Ir. H. Djuanda.